Entry modes and key local practices of international super-deluxe hotel chains in South Korea - Lee, Cheow Jin (2008)
In our study, we reviewed business practices adopted by global hotel chains, gathered relevant information from secondary sources, and conducted interviews and surveys with hotels and various related organisations in Singapore and South Korea.